Optically responsive delivery platforms: from the design considerations to biomedical applications - Koryakina I. Irina; Kuznetsova D. Darjya; Zuev D. Dmitry; Milichko V. Valentin; Timin A. S. Aleksandr Sergeevich; Zyuzin M. V. Mikhail (2020, 2020)
Title screen